(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Dissection of cadaveric temporal bones in a laboratory for temporal bones is an essential component of teaching safe, competent otorhinolaryngologists. Recent organ retention problems have resulted in a diminished supply of temporal bones. Thus, contemporary trainees dissect far fewer bones than their mentors. We explain the construction of a temporal bone laboratory in the Department of Anatomy at University College, beginning with the timely preparation and preservation of tissue and ending with its disposal. Comparisons are made between our experience and training programmes. The laboratory for temporal bones is the only one. The exposure and experience gained by rotating registrars has resulted in considerable improvements in their operational skills. The laboratory for temporal bone remains an essential component of training. It is hoped that this publication will help other units overcome barriers to create a laboratory for temporal bone research.